Effectiveness of Squat and Countermovement Jumps in Improving Vertical Jump Performance (British Journal of Multidisciplinary and Advanced Studies, 2024)
Vertical jump is an essential component for success in sports and athletic performance. This study determined the effectiveness of squat and countermovement jumps in improving vertical jump performance of Tertiary Athletes in one of the Universities in Cagayan de Oro City for School Year 2018-2019. This study utilized quasi-experimental design (pretest and posttest) where two treatment groups were involved. There were seventy-four (74) athletes who participated and they were distributed into two groups with specific exercise routines such as squat jump and countermovement jump. Findings reveal that there was a significant increase in the vertical jump performance of the athletes after exposure to the two exercise routines. This study concluded that both half squat jump and countermovement jump enhanced the vertical jump performance of the tertiary athletes. The study further established that both squat jump and countermovement jump was comparably effective in improving the vertical jump performance of the participants. It is recommended that the two exercise routines will be integrated in the varsity training program as well as in the physical education classes to improve the vertical jump performance of both athletes and the students.